Feel Safe: A pilot study of a protective behaviours programme for people with intellectual disability - Mazzucchelli, Trevor (Taylor & Francis, 2001)
A pilot study of a group programme designed to increase personal safety skills in adults with an intellectual disability is described. Feel Safe, a curriculum based on Flandreau-West's protective behaviours anti-victimisation and empowerment process, aims to teach the protective behaviours themes "we all have the right to feel safe all the time" and "nothing is so awful that we can't talk with someone about it"; how to recognise unsafe situations; and a range of personal coping and problem-solving skills. A quasi-experimental control group design (10 adults in each group) with pre-test, post-test, and follow-up assessments aimed to determine whether participants attending the Feel Safe programme understood and retained the content of sessions, increased their use of protective behaviour skills and concepts, and perceived themselves as being safer and more satisfied with how safe they felt. The results were promising. They suggested that by attending the Feel Safe programme people could increase their knowledge in their day-to-day lives. Participants in the experimental group were not found, however, to perceive themselves as being safer or more satisfied with how safe they felt. Psychometric properties of two new instruments to assess knowledge and use protective behaviours skills were also investigated and are reported.